Abstracts Accepted for Publication 2017
DOI: 10.1136/annrheumdis-2017-eular.5380
|View full text |Cite
|
Sign up to set email alerts
|

AB1207-HPR Patient satisfaction in a rheumatoid arthritis specialized center

Abstract: BackgroundAccording to the Beryl Institute's, patient experience (PX) is “the sum of all interactions, shaped by an organization's culture, that influence patient perceptions, across the continuum of care”; nowadays patient satisfaction is considered as one of the quality for performance in health systems (1). In order to provide a multidisciplinary quality care to patients with RA in centers of excellence (CoEs) under the coordination of a rheumatologist, provide comprehensive management of patients with this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Raw as generally high with treatment. 28,29 Many studies used homemade questionnaires, [30][31][32][33][34][35] and only one of them used a rigorous method for developing the questions. 30 They generally showed that the patients' satisfaction was high, but that some expectations were not always met.…”
Section: Discussionmentioning
confidence: 99%
“…Raw as generally high with treatment. 28,29 Many studies used homemade questionnaires, [30][31][32][33][34][35] and only one of them used a rigorous method for developing the questions. 30 They generally showed that the patients' satisfaction was high, but that some expectations were not always met.…”
Section: Discussionmentioning
confidence: 99%